Effect of tool wear on microrods fabrication using reverse μEDM. Issue 3 (17th February 2017) - Singh, Amit Kumar; Patowari, Promod Kumar; Deshpande, Nishikant V.
ABSTRACT: Arrayed microrods are used to drill array of microholes in workpieces by Micro electrical discharge machining (μEDM). In comparison to a single microrod, the use of an array of microrods enables drilling of multiple microholes in lesser time, and hence it offers a higher productivity. The present work focuses on the effect of tool wear on the dimensions of the machined array of microrods through reverse micro electrical discharge machining (R - μEDM). The effects of the input parameters such as voltage, capacitance and feed rate on the obtained length and diameter of the microrods have been investigated. This study introduces a simple analytical model to evaluate the amount of tool wear and material removal from a bulk rod. As the levels of voltage and capacitance increase from lower to higher, the tool wear increases by 574%. At lower levels of voltage and capacitance, a straight array of microrods with a longer length of about 1.961 mm is obtained. On the other hand, at higher levels of voltage and capacitance, the obtained microrods are found to have a shorter length of 1.725 mm but with taper. Scanning electron microscope (SEM) and optical microscope images are also analyzed for describing the effects of tool wear on the shape and size of the fabricated microrods.